Curriculum guide for teaching house officers and faculty: applying procedure codes effectively using chemical denervation as a model - Berri, Maryam; Beydoun, Noha; Johnson, Martha (Frontiers in Medicine, 2024)
Introduction: The health care system in the United States relies on provider driven initiation of billing and coding for collection of payment and professional fees. Under the umbrella of practice management is the ever changing and sub-optimally taught concept of procedural billing and coding to House Officers, and faculty. Clinical providers initiate billing and coding for the performed procedural encounter, supported by the appropriate documentation. Correct charge capture is dependent on linking appropriate CPT code, J codes that include documentation of waste, modifiers and to collect charges. We discuss a perspective regarding a new curricular methodology that teaches learners to apply an algorithmic approach to correctly code CPT code, J code, and modifier to chemical denervation procedure with high cost Botulinum Toxin. We further recommend use of visuals with algorithm development for other pertinent procedures that is specific to a department. Methods: We developed a curriculum that includes an algorithmic visual, pre & posttest questions, and reflections. It was implemented across various learner types. Results: This chemical denervation curriculum was impactful in meeting the objectives of the course and expanded a learners vision on practice management in that this educational method can be applied to other procedures. Discussion: The results demonstrate a clear gap in practice management education as the pre-course knowledge to apply appropriate codes was low. Learners indicated that especially valuable was the algorithm, which we developed as a tool practitioners can utilize to appropriately account for all aspects of procedural coding; CPT, modifiers and J-codes.